Does leptin cause an increase in blood pressure in animals and humans?. Issue 1 (January 2017) - Simonds, Stephanie E.; Pryor, Jack T.; Cowley, Michael A.
Abstract : Purpose of review: Cardiovascular diseases (CVDs) are the number one cause of death globally. The risk for the development of CVDs is significantly increased in obesity. Leptin, the product of white adipose tissue, appears to contribute to the development of CVDs in obesity. Here, we discuss the premise that leptin engages the sympathetic nervous system and contributes to elevated blood pressure (BP) developing in obesity. Recent findings: The long-term regulation of BP is dependent on the activity of the autonomic nervous system and specifically the sympathetic nervous system. Sympathetic nerve activity is significantly increased in obese rodents and humans. Leptin increases sympathetic nerve activity in rodents and humans; however, leptin only consistently increases BP chronically in rodents. The ability of leptin to increase BP in rodents is via both hypothalamic and extrahypothalamic regions. In leptin-deficient and leptin receptor-deficient humans, leptin appears to be the key reason for decreased systolic BP. However, in other research conducted in humans, chronic administration of leptin does not elevate BP. Summary: Further research into the role of leptin in the development of CVDs, especially in humans, needs to be conducted.